Synflorescence Architecture studies in some Indian Cypereae (Cyperaceae) - Desai, Rinku J.; Raole, Vinay M. (Rheedea, 2014)
The tribe Cypereae comprises 19 genera and 900 species, of which the genus Cyperus is the largest having a cosmopolitan distribution. There are differences in opinion on the delimitation of the genus. The comparative typological analysis of synflorescence has proved to be a major source of reliable diagnostic traits for the same. In this context, synflorescence variations in more than 35 taxa of Cypererae. were analyzed during present investigations and systematic value is discussed in detail. In the phenetic analyses all the studied taxa were grouped in to two major groups based on synflorescence and achene characters. Furthermore, type of inflorescence, rachilla disarticulation and spikelet prophylls are found to be most functional characters. The results show Cyperus s.s. to be polyphyletic, and merging of all the segregated taxa into Cyperus s.l. and recognizing as subgenera would make a monophyletic entity.